An Improved Capillary Pressure Model for Fractal Porous Media: Application to Low-Permeability Sandstone - Muhammad Saafan; Mysara Mohyaldinn; Khaled Elraies (Journal of Engineering and Technological Sciences, 2022)
Capillary pressure is a crucial input in reservoir simulation models. Generally, capillary pressure measurements are expensive and time-consuming; therefore, there is a limitation on the number of cores tested in the laboratory. Accordingly, numerous capillary pressure models have been suggested to match capillary pressure curves and overcome this limitation. This study developed a new fractal capillary pressure model by depicting the porous system as a bundle of tortuous triangular tubes. The model imitates the pores’ angularity, providing a more accurate representation of the pore system than smooth circular openings. Moreover, triangular tubes allow the wetting phase to be retained in the tube’s corners. A genetic algorithm was employed to match the capillary pressure curves and obtain the proposed model’s parameters. Capillary pressure data of eight low-permeability sandstone samples from the Khatatba formation in the Western Desert of Egypt were utilized to test the proposed model. The results revealed that the developed model reasonably matched the laboratory-measured data.